Meta-Analysis the Association between Obesity and Periodontitis in Adults - Lia Khairunnisa; Yulia Lanti Retno Dewi; Eti Poncorini Pamungkasari (Masters Program in Public Health, 2021)
Background: The risk of periodontal disease was 2.9 times higher in the obese group compared to the normal group. Periodontitis is one of the 10 most common chronic diseases affecting the world's population. Obesity contri